Analyzing the dynamics of import demand function in Pakistan: Long-term and short-term relationships with key economic factors - Ahmad, Shakil; Maqbool, Imran; Raihan, Asif; Xin, Liu (Asian Journal of Economics and Empirical Research, 2024)
This study investigates the short-term and long-term correlations between total imports in Pakistan and a set of explanatory variables. We utilized the Autoregressive Distributed Lag (ARDL) model, and we estimated the import demand function for the period from 1980 to 2021. The Augmented Dickey-Fuller (ADF) test confirmed that none of the variables exhibited second-order integration, ensuring their suitability for the ARDL approach. Bounds testing indicated the existence of a long-term equilibrium relationship among the included variables. Furthermore, diagnostic tests validated our model's statistical robustness, ensuring our findings' reliability. The long-term analysis shows significant relationships between imports and key economic indicators such as gross domestic product (GDP), the inflation rate, and the import demand function. Furthermore, we found a slight positive impact on import demand from the import price index and foreign direct investment (FDI). These results emphasize the included relationships between various macroeconomic factors and import demand in Pakistan. Based on these findings, we recommend that the government implement policies aimed at boosting investment, stimulating economic growth, and controlling inflation. Specifically, policies that target enhancing foreign direct investment (FDI), maintaining stable inflation rates, and promoting economic growth will be crucial in strengthening the import demand function. These measures will not only support sustainable economic development but also optimize the import dynamics in Pakistan’s economy.